Pengaruh Variasi Kampuh Las dan Arus Listrik Terhadap Kekuatan Sambungan Las (Metal Inert Gas) MIG Pada Aluminium AA6063 - Asrul (P3M Politeknik Negeri Cilacap, 2025)
Aluminium has beneficial characteristics such as corrosion resistance, heat conductivity, electrical conductivity, and lightweight. However, when looking at steel materials, aluminum has unfavorable welding properties. The selection of welding amperage and additives compatible with the parent metal can influence welding joints. The purpose of this study was to determine the effect of the strength of MIG welding joints of AA6063 aluminum alloy on the variation of groove welding with electric current. The test data shows a value equal to 1. The highest tensile test value using X camphor at an electric current of 150 amperes is 14.05 kg/mm², and the lowest tensile stress value with K camphor at a current of 155 amperes is 6.75 kg/mm². 2. The test results of the highest hardness value with the V shank at a current of 160 amperes, namely 87.09 HRB in the weld metal area, then the HAZ area decreased in hardness value, namely 76.33 HRB, and the parent metal area increased again in value, namely 78.80 HRB and 3. These results show that welding with an X shank is better than a V shank and a K shank based on the electric current in the test results.